INTEGRATION OF COMPUTER TECHNOLOGIES SMK: AUTOMATION OF THE PRODUCTION CERTIFICA-TION PROCEDURE AND FORMING OF SHIPPING DOCUMENTS - S. A. Pavlenko (Литьë и металлургия)
Integration of informational computer technologies allowed to reorganize and optimize some processes due to decrease of circulation of documents, unification of documentation forms and others.